2019
DOI: 10.1177/0894845319840437
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Happiness, Social Support, and Future Time Orientation in Career Adaptability

Abstract: In the 21st century, young adult people who are prepared for the world of work are expected to be individuals who have the responsibility to manage their careers and have career adaptability skills. In this regard, it seems useful to understand the factors that may affect career adaptability. The purpose of this study was to investigate whether the happiness, social support, and future time orientation can predict career adaptability of young adults. The participants consisted of 525 students (389 female and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
(73 reference statements)
0
23
0
4
Order By: Relevance
“…CCT (Savickas, 2005, 2013) draws a map from adaptive readiness to adaptability resources, adapting responses, and adaptation results. Although previous studies have shown that career adaptability is significantly related to happiness (Öztemel & Yıldız Akyol, 2019), self-esteem (Cai et al, 2015; Marcionetti & Rossier, 2019), and career decision-making difficulties (Karacan-Özdemir, 2019), the number of research studies that test the full model is still limited. The present study demonstrates how adaptive readiness affects adaptation results indirectly, and it provides important clues about the mechanisms that support the adaptation results (happiness) of high school students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCT (Savickas, 2005, 2013) draws a map from adaptive readiness to adaptability resources, adapting responses, and adaptation results. Although previous studies have shown that career adaptability is significantly related to happiness (Öztemel & Yıldız Akyol, 2019), self-esteem (Cai et al, 2015; Marcionetti & Rossier, 2019), and career decision-making difficulties (Karacan-Özdemir, 2019), the number of research studies that test the full model is still limited. The present study demonstrates how adaptive readiness affects adaptation results indirectly, and it provides important clues about the mechanisms that support the adaptation results (happiness) of high school students.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth and final dimension of the model, adaptation results, was attempted to be measured with happiness. Previous research revealed positive correlations between career adaptability and optimism (e.g., Buyukgoze-Kavas, 2016), life satisfaction (e.g., Hirschi, 2009), and happiness (Öztemel & Yıldız-Akyol, 2019; Sattar et al, 2017). Furthermore, Perera and McIlveen (2017) stated that positive results such as happiness may indicate adaptation results.…”
Section: Introductionmentioning
confidence: 96%
“…Sahabat yang baik akan membantu para pelajar dalam situasi-situasi genting seperti apabila mereka mempunyai masalah yang tidak dapat diselesaikan sendiri. Sokongan baik yang diterima mampu mempengaruhi para pelajar untuk lebih yakin dengan keputusan yang dibuat dan akan sentiasa berusaha untuk mencapai kejayaan dalam perubahan kerjaya (Öztemel & Yıldız-Akyol, 2019).…”
Section: Perbincangan Kajianunclassified
“…Similar support may be offered from sources such as teachers or counsellors (e.g., , institutional support (e.g., Clair et al, 2017), peers (e.g., , and during classes (Lazarides, Rohowski, Ohlemann, & Ittel, 2016). As a whole, social support assists the development of career preparedness attitudes (e.g., Öztemel & Yıldız-Akyol, 2019;Ataç, Dirik, & Tetik, 2017) and helps adolescents to be more engaged in the process of making a career decision (Hirschi, Niles, & Akos, 2011).…”
Section: Contextual Predictors Of Career Preparednessmentioning
confidence: 99%